2016
DOI: 10.1038/srep37156
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of adsorbed polymers on attractive homogeneous surfaces

Abstract: Dynamic behaviors of polymer chains adsorbed on an attractive, homogeneous surface are studied by using dynamic Monte Carlo simulations. The translational diffusion coefficient Dxy parallel to the surface decreases as the intra-polymer attraction strength EPP or the polymer-surface attraction strength EPS increases. The rotational relaxation time τR increases with EPS, but the dependence of τR on EPP is dependent on the adsorption state of the polymer. We find that τR decreases with increasing EPP for a partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The results show that the diffusion of polymer is dependent on the conformation of polymer, in agreement with previous Monte Carlo simulation. It was found that the diffusion coefficient of polymer was low for a compact conformation in solution or on flat surface [26]. We have also checked the effect of NP's size on the diffusive property of polymer chain at the same concentration of NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the diffusion of polymer is dependent on the conformation of polymer, in agreement with previous Monte Carlo simulation. It was found that the diffusion coefficient of polymer was low for a compact conformation in solution or on flat surface [26]. We have also checked the effect of NP's size on the diffusive property of polymer chain at the same concentration of NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of polymers onto a planar surface has been studied for several decades [1][2][3][4][5][6][7][8], not only because it is of long-standing interest in polymer physics, but also because it is important in biological interactions [9][10][11]. While early researches focus more on polymers adsorbed on flat rigid surfaces [1,2,7], polymer adsorption on heterogeneous surface attracts more interest [4,5,8,12,13], as many naturally occurring surfaces are energetically inhomogeneous [4]. Chang et al [14] observed that λ-DNA molecules exhibit sub-diffusion on supported cationic lipid membranes by fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous simulation studies have mainly concentrated on polymer adsorption to flat or crystalline surfaces. , However, surface roughness and chemical heterogeneity are expected to play critical roles in determining interfacial properties. Studies that have compared polymer adsorption onto different surfaces have demonstrated marked differences in the polymer–solid interfacial structure, such as the local polymer density at the interface and orientation of vinyl functional groups .…”
Section: Introductionmentioning
confidence: 99%